The Implementation of Discipline Character Education in Shaping Students’ Behavior During the Learning Process in Grade 5 of SD Negeri 07 Enam Lingkung - Amelia Putri Wahyuni; Stavinibelia Stavinibelia; Ayunis Ayunis; Gingga Prananda (The Future of Education Journal, 2025)
This research is motivated by the importance of disciplinary character education as a foundation in fostering the behavior of elementary school students. Discipline is considered a basic value that forms order, responsibility, and compliance with the rules required in the learning process. The purpose of this study is to determine the implementation of disciplinary character education on fostering the behavior of students in grade 5 of SD Negeri 07 Enam Lingkung, to determine the factors that influence the fostering of disciplinary behavior and to determine the impact of the implementation of disciplinary character education. The research method used is qualitative through observation, interviews, and documentation. The results of the study indicate that the implementation of disciplinary character education went quite well and had a positive impact on students, such as teacher role models, the implementation of rules, and coaching strategies. In conclusion, disciplinary character education has a positive impact on the order, responsibility, and orderly attitudes of students, although it still needs to be strengthened through cooperation between schools and families.